HADIS DALAM TINJAUAN HISTORIS - Martono Martono (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
This research aims to analyze, understand and describe about studying the history of hadith from time to time. It is hoped that this article can be an entry point in studying other hadith sciences, both their distribution, which is seen from quantity narrator or quality. The method used in this research is library research by collecting various books, journals and scientific works other. The result of this discussion is that the development of hadith at this time, the Muslim community still lacks understanding of hadith and writing hadith. The conclusion from this discussion is that the Prophet always emphasized to friends to always understand the hadith and convey it to Muslims. It can be said that the Companions themselves have received a lot of hadith and some have received a few due to factors where they live, area, age and so on. One of the Prophet's greatest policies regarding the maintenance of both was to order his companions to memorize and write the Qur'an. Many of the Prophet's companions had collected many of the Prophet's hadiths, so the tabi'in, who were actually the companions' students, also collected many of the Prophet's hadiths, even these collections were arranged in regular books.